(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
The Prespa Agreement (PA) between Athens and Skopje was meant to be a final solution to the ‘name issue’. Yet the dispute has never been only about the state name, which is proved by the 20-pages long text. A plethora of other provisions is to be implemented erga omnes (internationally and domestically). Despite the insistence of the external mediators that the name dispute has never concerned the issues of ethnicity, nationality, culture, and language, these issues indeed appear to be simultaneously central as well as the Achilles heel of the deal. This paper does not deal with conceptual and theoretical aspects of ethnicity and nationality; yet its focus is on the fact that the Agreement indeed regulates identity issues; i.e. it represents a legal intervention in spheres pertaining to both ethnicity and national identity with implications for each. The basic premise is that instead of being a final solution to a protracted identity conflict, the PA symbolically reconceives the old Macedonian Question into a new form with an old essence. Thus, it does not resolve but rather complicates the identity security dilemma.